PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN (PKn) DENGAN MENGGUNAKAN MODEL COOPERATIVE LEARNING TIPE CO OP CO OP DI KELAS IV SEKOLAH DASAR - SARI, YONA MAYANG (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This research based on reality observed by writer at SDN 10 Surau Gadang, learning proses of PKn in fourth grade showed that student involvement was still low, where student lacked the courage to speaking to express their opinion, student lack of mutual help and coorperation and teacher also lack of using learning model that can stimulate student activity. There for researcher used learning model Cooperative Learning type Co Op Co Op to increase student learning outcomes. The objective of this research was to describe the increasing of student learning outcomes in PKn subject by using learning model Cooperative Learning type Co Op Co Op in fourth grade student. This research was class action research by using qualitative and quantitative approach,subjects of this research were fourth grade student of SDN 10 Surau Gadang and teacher of  fourth grade. Learning model used was Cooperative Learning type Co Op Co Op and consist of cycle I and cycle II. The data was obtained by observation and test. Result of this research showed that: a) cycle I planning, the average of meeting I with percentage 85% and meeting II was 92%, in cycle II increased to 96% and, b) implementation cycle I the average teacher factor in meeting I was 72%  and meeting II was 87% and increased in cycle II to 95% and student aspect cycle I the average of meeting I was 72% and meeting II was 85%  and increased in cycle II was 93%, c) student learning outcomes was obtained from three aspect cognitive, affective, psychomotor in cycle I was 68,17 and cycle II the average increased to 82,77. From this research we can conclude that by using learning model Cooperative Learning type Co Op Co Op can increased student learning outcomes in PKn at fourth grade SDN 10 Surau Gadang Kecamatan Nanggalo Kota Padang. Kata Kunci: hasil belajar.cooperative learning tipe co op co op,  hasil belajar.